DECONSTRUCTING STEREOTYPES: AN ANALYSIS OF LEILA AHMED'S FEMINIST PHILOSOPHY OF WOMEN IN ISLAM - Neng Nurya Safitri; Abdullah Abdul Kadir (Sadra International Institute, 2026)
Equality between men and women is a principle that should be upheld in social life, especially within muslim communities that believe both genders hold equal status before God. However, in reality, not all groups within muslim societies share this perspective. Some still adhere to doctrines that position women as subservient to men. In fact, equality does not necessarily mean identical sameness, but rather the acknowledgment of fair and proportional differences. This study aims to explore the thoughts of Leila Ahmed, a prominent muslim feminist, who offers a philosophical perspective on the position of women in Islam. This research employs a qualitative approach history and phenomenology. The findings reveal that Leila Ahmed’s ideas emphasize the importance of deconstructing deep-rooted stereotypes in Islamic understanding regarding women. She asserts that men and women possess equal status, even though they have different values and characteristics. These differences form the basis of their respective uniqueness. In conclusion, the concept of gender equality in Islam needs to be reexamined in depth to avoid generalizations and misunderstandings. Advocacy for gender equality must remain grounded in the fundamental values inherent in each gender, while respecting the distinct roles and responsibilities of both men and women in a just manner.